The role of gut hormonal aspect in Iraqi patients subjected to sleeve Gastrectomy (Baghdad Science Journal, 2024)
There are a variety of obesity surgeries and procedures in which obese individuals undergo. Primarily, they alter satiety and hunger hormone levels in the gut. Moreover, standard method of such procedures can result in long-term weight loss. Ghrelin (Ghr) is a gut hormone that regulates food intake. Laparoscopic Sleeve gastrectomy (LSG) is one method for treating morbid obesity (MO), which could modulate its secretion. The aim of the present study was to demonstrate the effect of sleeve gastrectomy on gut hormones. This study was conducted at Al-Basrah metabolic and Bariatric Surgery Center, Iraq, from December 2021 to March 2022, on 24 patients with morbid obesity treated by sleeve gastrectomy. The included patients were categorized into two main groups according to the periods of their operation. Glucagon –like peptide-1 GLP-1, Ghrelin, Leptin hormones and body mass index (BMI) were significantly decreased after surgery. There was a statistically significant correlation, found between patient's BMI and Leptin level after three months of the surgery, while a statistically significant correlation was found between patient's BMI and GLP-1 level before the surgery when BMI increase by one unit (Kg/m2), the GLP-1 would be increased by half unit 0.45 (50%). The present study has reported that the three hormones GLP-1, Ghrelin and Leptin were decreased after three months of the surgery.